2022
DOI: 10.1016/j.amsu.2022.103327
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia versus normothermia after out-of-hospital cardiac arrest: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background The current guidelines recommend targeted temperature management (TTM) as part of the post-resuscitation care for comatose patients following out-of-hospital cardiac arrest. These recommendations are based on the weak evidence of benefit seen in the early clinical trials. Recent large multicentered trials have failed to show a meaningful clinical benefit of hypothermia, unlike the earlier studies. Thus, to fully appraise the available data, we sought to perform this systematic review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Clinically, favorable neurologic outcome is defined by the mRS or CPC scores, which describe the functionality of a patient after suffering a neurologic injury [16,17]. Similar to previous meta-analyses, our meta-analysis revealed no overall neurologic benefit of therapeutic hypothermia when compared to normothermia [18][19][20][21][22][23]. TSA of favorable neurologic outcome demonstrated the futility of therapeutic hypothermia compared to normothermia, suggesting further randomized controlled studies should likely not be conducted with this outcome.…”
Section: Favorable Neurologic Outcomesupporting
confidence: 62%
“…Clinically, favorable neurologic outcome is defined by the mRS or CPC scores, which describe the functionality of a patient after suffering a neurologic injury [16,17]. Similar to previous meta-analyses, our meta-analysis revealed no overall neurologic benefit of therapeutic hypothermia when compared to normothermia [18][19][20][21][22][23]. TSA of favorable neurologic outcome demonstrated the futility of therapeutic hypothermia compared to normothermia, suggesting further randomized controlled studies should likely not be conducted with this outcome.…”
Section: Favorable Neurologic Outcomesupporting
confidence: 62%
“… 32 In addition, some other studies have shown different results, concluding that hypothermia does not improve patient outcomes, suggesting that more trials are needed in the future to determine the efficacy of clinical hypothermia treatment. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent comprehensive meta-analysis further indicated no differences in neurological or survival outcomes between targeted hypothermia (32-34 C) and normothermia (!36 C with fever control) for comatose OHCA patients. 23 The European Resuscitation Council-European Society of Intensive Care Medicine (ERC-ESCIM) guidelines still recommend TTM with a TFS. Active fever control with simple surface cooling using wet towels and ice can be considered in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent comprehensive meta-analysis further indicated no differences in neurological or survival outcomes between targeted hypothermia (32–34°C) and normothermia (≥36°C with fever control) for comatose OHCA patients. 23 …”
Section: Discussionmentioning
confidence: 99%